Dobra Nowina pomimo złych wieści (Mk 14,1-11) - Malina, Artur (Studia Pastoralne, 2026)
The subject of the study of the anointing at Bethany narrative (Mark 14:3-9), which is placed between two scenes depicting actions against Jesus: the conspiracy of the chief priests and scribes (Mk 14:1-2) as well as the departure of Judas to the chief priests (Mark 14:10-11). This inclusion belongs to a type of literary device which occurs frequently in the Gospel of Mark: an ongoing story is interrupted by another and is continued and completed once the middle story ends. The chief priests and scribes, who act as initiators and promoters of actions against Jesus, are joined by one of the Twelve. The contrast to these activities is not a people full of admiration for His teaching, but the actions of the woman in Bethany. In this way, her act becomes the content of the Good News proclaimed in spite of bad news about the role of His external and internal enemies. In all circumstances the disciple is called to follow the example of total and unconditional commitment to the Lord, which is presented as a memento for the addressees of the Gospel.